THE RELATIONSHIP OF GADGET ADDICTION ON MENTAL HEALTH IN MEDICAL STUDENTS - Anissa, Mutiara; Maska, Hadid Pratama; Ariwibawa, Tangguh; Abdullah, Dessy (MSJ : Majority Science Journal, 2024)
Smartphone, is a term to distinguish advanced feature phones from basic feature phones. Excessive smartphone use or addiction can lead to negative health consequences such as neck pain, accidents, anxiety, depression, and sleep disorders. This study aims to determine how the influence of gadget use addiction on mental health in medical students. Method used (narrative review/systematic review with PRISMA 2020). Research was collected through searches on Google Scholar from 2019 to 2023, Ebscho from 2019 to 2023 with full text limits and PubMed from 2019 to 2023. The keyword searches used are smartphone addiction, mental health, and medical student. 210 results were found from Google Scholar, 15 results were found on Ebscho, 31 results were found on PubMed, and 21 studies were included in the study. Results of the 256 journals netted, there are 21 journals that match the category of literature review titles. There is a significant relationship between gadget addiction to mental health in medical students, especially in women.